Pulp Screen Plugging Characteristics - Parsa Aryanpour; Robert W. Gooding; James A. Olson (BioResources)
Aperture plugging is a phenomenon that limits both the capacity and efficiency of pulp screens, which are critical components of the papermaking process. An understanding of how plugs are created and how they can be avoided can enhance the manufacture of paper products, providing energy savings, increased productivity, improved product quality, and higher levels of paper recycling. This work considers the creation and dispersion of plugs in a small, industrial screen. Flow resistance provides a means of assessing the presence of plugs and their evolution through creation and dispersion. A structured means of plug dispersion was formulated, from which floc strength could be inferred. These novel measurements provide insight not only into the factors that control plug creation, but into their character. Long-fiber (softwood) plugs were found to form and consolidate quickly and to achieve high strength. Their low porosity limited flow through the slot soon after creation. Short-fiber (hardwood) plugs formed more slowly, and they were more porous and weaker.